Special integrated cap for aluminum shell resistor and production process thereof

CN122658795APending Publication Date: 2026-08-28TAIWANGJIA (HUIZHOU) ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611080554.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种铝壳电阻专用一体帽及其生产工艺,解决了现有铝壳电阻一体帽因分体焊接导致的接触缝隙问题,以及在纯锡电镀时,由于深孔结构的电场屏蔽效应导致孔内镀层偏薄或漏镀,且外表面会产生树枝状结晶及锡须,进而造成产品的可靠性下降与抗氧化能力衰减的问题

Benefits of technology

[0031]1. This invention improves the uniformity of pure tin layer thickness in blind holes and deep holes and reduces plating defects by using a step-by-step electroplating process with a dual-tank heterogeneous system. The high-temperature anchoring solution in tank A uses sodium 3-mercapto-1-propanesulfonate for pre-adsorption at the bottom of the deep hole, while the low-temperature pulse solution in tank B uses the steric hindrance effect of macromolecular branched polyethyleneimine to form a polarization barrier layer on the exposed surface. This system difference makes the polarization overpotential inside the deep hole lower than that on the outer surface, which promotes the preferential reduction of free tin ions in the deep hole and fills it from bottom to top, thereby improving the uniformity of the inner and outer plating layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122658795A_ABST
    Figure CN122658795A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of electronic component manufacturing, and discloses a special integrated cap for aluminum shell resistors and a production process thereof, which comprises a bare integrated cap and a pure tin plating layer covering the surface of the cap. The plating layer is made by step-by-step plating of A-slot high-temperature fixed-planting liquid and B-slot low-temperature pulse liquid. The production process is as follows: low-carbon steel wires are continuously punched to form the bare integrated cap and pretreated; the cap is immersed in the A-slot high-temperature fixed-planting liquid to perform cathode direct-current barrel plating, so that the accelerator is pre-adsorbed in the deep hole; the liquid in the tank is taken out and exposed in the air to establish a chemical gradient of passivation outside the hole and activity inside the hole; then the cap is immersed in the B-slot low-temperature pulse liquid to perform barrel plating by using an outer surface barrier layer formed by branched polyethylene imine and an asymmetric reverse pulse power source; and finally, the cap is washed with water and dried by hot air centrifugal drying. The application cooperates a double-tank heterogeneous system with pulse plating to eliminate the contact resistance of split splicing, improve the plating leakage condition of deep holes and blind hole parts of the cap body, and improve the uniformity and firmness of the plating layer of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic component manufacturing technology, specifically to an integrated cap for aluminum-cased resistors and its manufacturing process. Background Technology

[0002] As a common type of power electronic component, aluminum-cased resistors have an integrated cap structure at both ends. This integrated cap is generally made of an iron cap body and an iron wire lead through a welding process. In order to ensure the solderability of the integrated cap in the subsequent circuit board mounting process, and at the same time improve the oxidation resistance of the iron substrate and the lead joint, a layer of pure tin electroplating needs to be deposited on the surface of the bare integrated cap during production.

[0003] Existing products and pure tin electroplating processes have the following technical defects when dealing with such integrated caps: On the one hand, traditional welding processes result in microscopic gaps at the junction of the cap and the lead wire, which not only easily hide electroplating residues but also easily generate contact resistance during use; on the other hand, and more significantly, the interior of the integrated cap has a deep blind hole structure for housing the resistor core. In the conventional single-tank DC barrel plating process, due to the electric field shielding effect inside the deep hole, the actual current density at the bottom of the hole is much lower than that on the exposed surface, making it difficult for free tin ions in the electroplating solution to be reduced and deposited at the bottom of the deep hole, thus causing the tin layer inside the deep hole to become thinner or even resulting in localized plating defects.

[0004] To compensate for insufficient plating thickness inside deep holes, conventional production methods include increasing the overall electroplating current density or extending the barrel plating time. However, this operation can lead to excessive tin ion deposition in high-current-density areas on the outer surface and edges of the integrated cap. Rapid local deposition on the outer surface can trigger the formation of dendritic crystals, reducing the density of the microstructure of the pure tin plating layer. Furthermore, during the release of internal stress in subsequent service, it can induce tin whisker growth. The dual defects of incomplete plating in deep holes and tin whisker growth on exposed surfaces ultimately result in high contact resistance, reduced oxidation resistance, and decreased reliability of downstream products in the integrated cap. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides an integrated cap for aluminum-cased resistors and its manufacturing process. It solves the problem of contact gaps caused by separate welding in existing integrated caps for aluminum-cased resistors, as well as the problem of thin or incomplete plating of the inner layer of the hole due to the electric field shielding effect of the deep hole structure during pure tin electroplating, and the generation of dendritic crystals and tin whiskers on the outer surface, which leads to a decrease in product reliability and a reduction in oxidation resistance.

[0006] To achieve the above objectives, the present invention provides the following technical solution: Firstly, the present invention provides an integrated cap for aluminum-cased resistors, comprising a bare integrated cap and a pure tin electroplating layer covering the surface of the bare integrated cap. The pure tin electroplating layer is prepared by step-by-step electroplating of a dual-tank pure tin electroplating solution composition comprising a high-temperature anchoring solution in tank A and a low-temperature pulse solution in tank B. Based on a total weight of 1000 parts of deionized water, the raw materials of the high-temperature anchoring solution in tank A include: 70 to 90 parts of methanesulfonic acid; 35 to 45 parts of tin methanesulfonate; 0.5 to 1.2 parts of sodium 3-mercapto-1-propanesulfonate; and 0.8 to 1.5 parts of catechol. Based on a total weight of 1000 parts of deionized water, the raw materials of the low-temperature pulse solution in tank B include: 70 to 90 parts of methanesulfonic acid; 35 to 45 parts of tin methanesulfonate; and 1.0 to 2.0 parts of branched polyethyleneimine.

[0007] By adopting the above technical solution, the use of a dual-tank heterogeneous system for stepwise electrodeposition is beneficial to improving the uniformity of the coating inside and outside the deep hole. Regarding the electrodeposition and film formation mechanism, the high-temperature anchoring solution in tank A does not contain macromolecular inhibitors. Under heating conditions, the viscosity of the system decreases and the diffusion coefficient of ions increases. Sodium 3-mercapto-1-propanesulfonate, as an electroplating accelerator, has a good chemical adsorption tendency for the low-carbon steel substrate due to the thiol functional group in its molecular structure. Driven by thermodynamic kinetic energy, sodium 3-mercapto-1-propanesulfonate can overcome the mass transfer resistance in the blind hole and penetrate to the bottom of the deep hole, where it undergoes specific adsorption on the surface of the bare integrated cap substrate. This provides a reducing environment for catechol in the system, preventing divalent tin ions from hydrolyzing or being oxidized to tetravalent tin at high temperatures, thus maintaining the concentration of free tin ions. As a result, an active base film rich in accelerators is constructed on the inner wall of the deep hole of the bare integrated cap.

[0008] After entering the low-temperature pulsed liquid in tank B, due to the introduction of branched polyethyleneimine, the macromolecular chain segments curl up and the diffusion rate is slow in the low-temperature environment. The branched polyethyleneimine is mainly physically adsorbed on the exposed surface of the bare cap and in the high current density area, making it difficult to enter the deep hole in large quantities. The dense amino groups complex with divalent tin ions, forming a polarization barrier layer with high charge density on the outer surface, which increases the tin deposition overpotential on the outer surface. At this time, the deep hole maintains a low polarization overpotential due to the pre-adsorption of sodium 3-mercapto-1-propanesulfonate. Therefore, the reduction rate of tin ions in the hole is greater than that on the outer surface. This bottom-up filling method helps to improve the deep hole plating failure.

[0009] Preferably, the branched polyethyleneimine has a weight-average molecular weight of 600 to 1000.

[0010] By adopting the above technical solution, the molecular weight is controlled within the range of 600 to 1000, which can regulate the electrochemical polarization state to a certain extent. When the weight-average molecular weight is below 600, the polymer chain segments are relatively short, and the steric hindrance formed on the outer surface is insufficient, making it difficult to suppress the rapid reduction of metal ions on the outer surface. When the weight-average molecular weight is above 1000, the hydrodynamic radius of the polymer increases, which leads to an increase in the viscosity of the bath solution and aggregation under the action of the electric field, causing inclusions, pores and fogging phenomena in the outer surface coating. Limiting the above molecular weight range helps the inhibitor molecules form a denser adsorption layer on the outer surface, ensuring the density of the pure tin layer crystallization.

[0011] Preferably, the branched polyethyleneimine is made from the following raw materials in parts by weight: 85.0 to 115.0 parts of deionized water; 1.5 to 2.4 parts of p-toluenesulfonic acid monohydrate; and 6.5 to 11.2 parts of ethyleneimine monomer.

[0012] By adopting the above technical solution, an electroplating inhibitor with high branching degree and rich in secondary and tertiary amine structures is synthesized. The p-toluenesulfonic acid monohydrate dissociates into acidic protons in deionized water, which serve as an initiator for cationic ring-opening polymerization. The nitrogen atom in the ethyleneimine monomer molecule is protonated and attacked to form a reactive three-membered heterocyclic quaternary ammonium cation. The unprotonated ethyleneimine monomer in the system uses the lone pair electrons on the nitrogen atom to nucleophilically substitute and attack the protonated three-membered ring, causing the carbon-nitrogen bond to break and initiating ring-opening polymerization.

[0013] As hydrogen atoms on the amino group are continuously replaced during the reaction, the polymerization reaction is accompanied by chain transfer and branching processes, forming a hyperbranched three-dimensional network structure containing primary, secondary, and tertiary amines. The high-density nitrogen atom arrangement enhances the multidentate complexation coordination ability between the polymer and the metal matrix, thereby improving the adsorption strength of polyethyleneimine as an electroplating inhibitor.

[0014] Preferably, the bare integrated cap is made of low carbon steel wire with a diameter of 1.6 to 2.2 mm by continuous stamping and integral forming. One end of the bare integrated cap is the formed cap body, and the other end is the retained lead wire. The end of the lead wire is provided with a flattened part, and the flattened part is punched with a mounting round hole with a diameter of 1.5 to 2.2 mm.

[0015] By adopting the above technical solutions, limiting the wire diameter and integral molding structure of low-carbon steel wire raw materials helps to improve the overall mechanical strength of the product. The uniform ferrite structure inside the low-carbon steel wire not only gives the material excellent cold work ductility, ensuring that no micro-cracks are generated during the severe continuous cold stamping deformation process, but also, compared with ordinary commercially available iron wire with more impurities and unstable carbon equivalent, the low-carbon steel matrix can expose more uniform and pure metal bonds after pickling and activation, enhancing the underlying physical anchoring force between the subsequent pure tin plating layer and the substrate. Using a single low-carbon steel wire for continuous stamping integral molding avoids the micro-gaps at the contact interface caused by separate welding, fundamentally eliminating internal contact resistance. The size matching of the flattened part and the mounting hole provides a reliable mechanical interlocking structure for subsequent external circuit assembly, and improves the distribution of electric field lines at the edge of the hole during the electroplating process.

[0016] Secondly, the present invention also provides a manufacturing process for an integrated cap for aluminum-cased resistors, comprising the following steps:

[0017] Low-carbon steel wire is selected as the raw material. First, one end of the low-carbon steel wire is formed into a cap body through continuous stamping. Then, the wire is cut, and the unstamped end is retained as a lead wire. Next, the end of the lead wire is flattened and punched to obtain a bare integrated cap. High-temperature fixation solution A and low-temperature pulse solution B are prepared separately. The bare integrated cap undergoes pretreatment sequentially, including alkaline degreasing, water washing, dilute sulfuric acid pickling at room temperature, and water washing. The pretreated bare integrated cap is first immersed in the heated high-temperature fixation solution A for cathodic DC barrel plating. Then, the solution is removed and exposed to air for a set time. Next, it is quickly immersed in the cooled low-temperature pulse solution B and barrel plating is performed using an asymmetric reverse pulse power supply. Finally, it is removed, washed with water, and dried by hot air centrifugal drying to obtain a dedicated integrated cap for aluminum-cased resistors.

[0018] By adopting the above technical solution, it is beneficial to obtain electroplated products with uniform thickness and fine crystals. The pretreatment process removes the grease and oxide layer on the substrate surface through alkaline saponification and acidic proton replacement reaction, exposing the metal lattice. In the cathode DC barrel plating stage, a continuous DC electric field is applied to drive sodium 3-mercapto-1-propanesulfonate to overcome the fluid retention layer in the micropores, realizing the chemical anchoring of the accelerator at the bottom of the deep hole. During the process of removing the bath solution from the bare cap and transferring it to the air for exposure, the liquid film on the outer surface directly undergoes mass transfer exchange with oxygen in the air. Catechol, as an antioxidant, preferentially undergoes redox reaction with the permeated oxygen on the outer surface to consume dissolved oxygen, while causing slight oxidation passivation of the accelerator attached to the outer surface.

[0019] Due to capillary effect and spatial confinement, the interior of deep holes is in a relatively oxygen-deficient state, which preserves the activity of the accelerator. This creates an electrochemical gradient where the outside of the hole is passivated while the inside remains active. When the hole enters the B-tank and is barrel-plated using an asymmetric reverse pulse power supply, the forward pulse provides a periodic high instantaneous current, which promotes the free tin ions to penetrate the double layer and nucleate inside the hole. The reverse pulse causes anodic dissolution of the plating layer in a short time. The microscopic protrusions on the outer surface are preferentially stripped due to the concentration of electric field lines, while the co-deposited hydrogen is desorbed. The alternating action of the pulses can reduce concentration polarization, interrupt the epitaxial growth direction of the crystal, and finally form a dense tin plating layer with preferred orientation.

[0020] Preferably, in the pretreatment, the following steps are performed sequentially: alkaline degreasing at 45 to 55°C for 4 to 8 minutes, water washing, acid washing with dilute sulfuric acid at room temperature with a mass concentration of 8% to 12% for 1.5 to 3 minutes, and water washing.

[0021] By adopting the above technical solution, the surface cleanliness and roughness can be improved. The alkaline system provides activation energy within this temperature range, causing the unsaponifiable oil to emulsify and the saponifiable oil to undergo hydrolysis. The dilute sulfuric acid with a concentration controlled at 8% to 12% can dissolve the oxides on the surface of the low-carbon steel substrate to form soluble ferric sulfate salts, while not causing excessive corrosion and hydrogen embrittlement of the substrate. The above pretreatment operation provides a pure crystal surface for the subsequent specific adsorption of accelerators.

[0022] Preferably, in the cathode DC barrel plating, the constant temperature of the high-temperature planting solution in tank A is controlled at 40 to 50°C, and the cathode DC current density is 0.4 to 0.6 A / dm³. 2 The barrel plating time is 2 to 4 minutes.

[0023] By employing the above technical solution, the pre-adsorption of the accelerator inside the blind pores is promoted. Setting the temperature to 40-50℃ increases the thermal motion rate of molecules within the system and reduces the fluid viscosity within the micropores, thereby increasing the mass transfer flux of sodium 3-mercapto-1-propanesulfonate diffused into the microscopic deep pores to 0.4-0.6 A / dm³. 2 The low current density limits the rapid nucleation and deposition of tin metal, allowing accelerator molecules time to coordinate and bond on the metal substrate, preventing premature closure of the crystal nuclei and blockage of the mass transfer channels within the pores.

[0024] Preferably, the set time for the naked cap to be exposed to air is controlled between 10 and 20 seconds.

[0025] By adopting the above technical solution, a reasonable activity difference gradient can be established between the outside and inside of the hole. When the exposure time is less than 10 seconds, the oxygen mass transfer at the gas-liquid interface is not sufficient, making it difficult to passivate the external surface accelerator. When the exposure time is more than 20 seconds, excessive evaporation of the liquid film will lead to the precipitation of salt crystals and the oxidation of divalent tin ions, which will cause the coating adhesion to decrease during subsequent pulse electroplating. The control range of 10 to 20 seconds can maintain the electrochemical reaction activity at the bottom of the deep hole while attenuating the external surface activity.

[0026] Preferably, when using an asymmetric reverse pulse power supply for barrel plating, the constant temperature of the low-temperature pulse solution in tank B is controlled to be 20 to 28°C; the parameters of the asymmetric reverse pulse power supply are set as follows: forward current density 1.2 to 1.8 A / dm³. 2 Reverse current density 3.6 to 5.4 A / dm 2 The forward time is 80 to 120 ms, the reverse time is 8 to 15 ms, and the continuous barrel plating time is 10 to 14 minutes.

[0027] By adopting the above technical solution, it is beneficial to generate a smooth and dense terminal coating. The low temperature setting of the B tank suppresses the thermal desorption of branched polyethyleneimine molecules, allowing them to adhere to the outer surface. In terms of electrical parameters, the forward time is controlled between 80 and 120 ms, providing conditions for tin ion discharge nucleation in the cathode diffusion layer. During the reverse time of 8 to 15 ms, a reverse pulse with a current density three times that of the forward pulse is applied, generating a tip peeling effect, preferentially dissolving the protruding crystal nuclei in the high current density region. This asymmetric charge cycle exchange removes free adsorbates from the crystal surface, forces the grains to grow in two-dimensional layers, and reduces the generation of dendritic crystals and grain boundary defects.

[0028] Preferably, in hot air centrifugal drying, the temperature of the hot air is controlled at 75 to 85°C.

[0029] By adopting the above technical solution, the risk of oxidation and discoloration and residual water marks on the surface of pure tin plating is reduced. Hot air at 75 to 85°C provides the latent heat required for moisture vaporization. Combined with the mechanical centrifugal force generated by the centrifugal equipment, the surface tension of water droplets in the deep hole is broken, allowing liquid water to leave the product surface. The temperature range is set below the recrystallization and rapid oxidation temperature threshold of tin. While achieving drying, it is beneficial to maintain the original metallic luster and adhesion of the plating.

[0030] This invention provides an integrated cap for aluminum-cased resistors and its manufacturing process. It offers the following advantages:

[0031] 1. This invention improves the uniformity of pure tin layer thickness in blind holes and deep holes and reduces plating defects by using a step-by-step electroplating process with a dual-tank heterogeneous system. The high-temperature anchoring solution in tank A uses sodium 3-mercapto-1-propanesulfonate for pre-adsorption at the bottom of the deep hole, while the low-temperature pulse solution in tank B uses the steric hindrance effect of macromolecular branched polyethyleneimine to form a polarization barrier layer on the exposed surface. This system difference makes the polarization overpotential inside the deep hole lower than that on the outer surface, which promotes the preferential reduction of free tin ions in the deep hole and fills it from bottom to top, thereby improving the uniformity of the inner and outer plating layers.

[0032] 2. This invention optimizes the microcrystalline state of the coating by controlling the transfer exposure time of the bare integrated cap in air and combining it with asymmetric reverse pulse electroplating. The brief air exposure utilizes the gas-liquid mass transfer difference to reduce the activity of the accelerator on the outer surface of the hole while maintaining electrochemical activity inside the hole. In the subsequent pulse barrel plating, the reverse high current density can preferentially dissolve the protruding crystal nuclei in the high current density area and promote hydrogen desorption, forcing the grains to grow in two-dimensional layers, reducing the generation of dendritic crystals and grain boundary defects, thereby improving the density of the pure tin coating and inhibiting the growth of tin whiskers.

[0033] 3. This invention enhances the overall mechanical bonding strength and robust reliability of the finished product by limiting the integral molding process and size matching of the bottom hardware parts and combining them with a specific temperature-controlled post-processing process. It uses a single low-carbon steel wire for continuous stamping and integral molding, avoiding the splicing gaps caused by traditional split processes, fundamentally eliminating the contact resistance between the cap and the lead wire, and improving the overall mechanical strength and conductivity of the hardware parts. At the same time, the 75 to 85°C hot air centrifugal drying operation after electroplating, under the condition of quickly removing moisture from deep holes by mechanical force, avoids the recrystallization of the tin layer and surface oxidation discoloration caused by high temperature, maintaining the metallic luster and reliability of the end product surface. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the AC impedance spectrum characteristics at the open circuit potential of the present invention;

[0035] Figure 2 This is a schematic diagram of the oxygen element depth profile curve of the present invention;

[0036] Figure 3 This is a schematic diagram showing the comparison of fluorescence signals deep inside the circular hole of the present invention;

[0037] Figure 4 This is a schematic diagram comparing the fluorescence signals at the outer edge of the present invention;

[0038] Figure 5 A schematic diagram of the integrated cap sample with added interfacial antioxidants according to the present invention;

[0039] Figure 6 This is a schematic diagram of the integrated cap sample of the present invention without the addition of interfacial antioxidants;

[0040] Figure 7 This is a planar schematic diagram of the integrated cap for aluminum-cased resistors according to the present invention. Detailed Implementation

[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0042] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0043] The CAS number for tin methanesulfonate is 53408-94-9;

[0044] The CAS number for methanesulfonic acid is 75-75-2;

[0045] The CAS number for sodium 3-mercapto-1-propanesulfonate is 17636-10-1;

[0046] The CAS number for catechol is 120-80-9;

[0047] The base material of the one-piece cap is commercially available conventional electroplated low-carbon steel wire with a wire diameter of 1.6mm to 2.2mm.

[0048] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.

[0049] Preparation Example 1:

[0050] This preparation example provides a method for preparing branched polyethyleneimine, including the following steps:

[0051] Add 100.0 parts of deionized water to a three-necked flask equipped with a stirrer, reflux condenser, thermometer and dropping funnel, then add 1.9 parts of p-toluenesulfonic acid monohydrate as a catalyst, turn on mechanical stirring and heat to 90°C.

[0052] 8.6 parts of ethyleneimine monomer were slowly added dropwise to a three-necked flask, with the addition time controlled at 2.0 h. During the addition, the temperature of the reaction system was maintained between 90 °C and 95 °C using a water bath.

[0053] After the addition was complete, the mixture was kept at a constant temperature of 90℃ for 1.2 hours to obtain the initial reaction solution.

[0054] The initial reaction solution was cooled to 25°C, and a 20% sodium hydroxide aqueous solution was added to adjust the pH of the system to 10.0 to deactivate the catalyst. The system was then placed in a rotary evaporator and subjected to vacuum distillation at 80°C under a gauge pressure of -0.09 MPa to remove water and unreacted monomers. The liquid at the bottom of the vessel was collected to obtain branched polyethyleneimine with a weight-average molecular weight of 800 for later use. This branched polyethyleneimine was named Branched Polyethyleneimine A.

[0055] Preparation Example 2:

[0056] This preparation example provides a method for preparing branched polyethyleneimine, including the following steps:

[0057] Add 85.0 parts of deionized water to a three-necked flask equipped with a stirrer, reflux condenser, thermometer and dropping funnel, then add 2.4 parts of p-toluenesulfonic acid monohydrate as a catalyst, turn on mechanical stirring and heat to 88°C;

[0058] 6.5 parts of ethyleneimine monomer were slowly added dropwise to a three-necked flask, with the addition time controlled at 1.5 h. During the addition, the temperature of the reaction system was maintained between 88 °C and 93 °C using a water bath.

[0059] After the addition is complete, continue stirring and maintaining the temperature at 88℃ for 1.0 h to obtain the initial reaction solution;

[0060] The initial reaction solution was cooled to 25°C, and a 20% sodium hydroxide aqueous solution was added to adjust the pH of the system to 10.0 to deactivate the catalyst. The system was then placed in a rotary evaporator and subjected to vacuum distillation at 75°C under a gauge pressure of -0.09 MPa to remove water and unreacted monomers. The liquid at the bottom of the vessel was collected to obtain branched polyethyleneimine with a weight-average molecular weight of 600 for later use. This branched polyethyleneimine was named Branched Polyethyleneimine B.

[0061] Preparation Example 3:

[0062] This preparation example provides a method for preparing branched polyethyleneimine, including the following steps:

[0063] Add 115.0 parts of deionized water to a three-necked flask equipped with a stirrer, reflux condenser, thermometer and dropping funnel, then add 1.5 parts of p-toluenesulfonic acid monohydrate as a catalyst, turn on mechanical stirring and heat to 92°C.

[0064] 11.2 parts of ethyleneimine monomer were slowly added dropwise to a three-necked flask, with the addition time controlled at 2.5 h. During the addition, the temperature of the reaction system was maintained between 92 °C and 97 °C using a water bath.

[0065] After the addition is complete, continue stirring and maintaining the temperature at 92℃ for 1.5 hours to obtain the initial reaction solution;

[0066] The initial reaction solution was cooled to 25°C, and a 20% sodium hydroxide aqueous solution was added to adjust the pH of the system to 10.0 to deactivate the catalyst. The system was then placed in a rotary evaporator and subjected to vacuum distillation at 85°C under a gauge pressure of -0.09 MPa to remove water and unreacted monomers. The liquid at the bottom of the vessel was collected to obtain branched polyethyleneimine with a weight-average molecular weight of 1000 for later use. This branched polyethyleneimine was named Branched Polyethyleneimine C.

[0067] Preparation Example 4:

[0068] This preparation example provides a method for preparing branched polyethyleneimine, including the following steps:

[0069] Add 95.0 parts of deionized water to a three-necked flask equipped with a stirrer, reflux condenser, thermometer and dropping funnel, then add 2.1 parts of p-toluenesulfonic acid monohydrate as a catalyst, turn on mechanical stirring and heat to 89°C;

[0070] 7.5 parts of ethyleneimine monomer were slowly added dropwise to a three-necked flask, with the addition time controlled at 1.8 h. During the addition, the temperature of the reaction system was maintained between 89 °C and 94 °C using a water bath.

[0071] After the addition was complete, the mixture was kept at a constant temperature of 89℃ for 1.1 h to obtain the initial reaction solution.

[0072] The initial reaction solution was cooled to 25°C, and a 20% sodium hydroxide aqueous solution was added to adjust the pH of the system to 10.0 to deactivate the catalyst. The system was then placed in a rotary evaporator and subjected to vacuum distillation at 78°C under a gauge pressure of -0.09 MPa to remove water and unreacted monomers. The liquid at the bottom of the vessel was collected to obtain branched polyethyleneimine with a weight average molecular weight of 700 for later use. This branched polyethyleneimine was named Branched Polyethyleneimine D.

[0073] Example 1:

[0074] This embodiment provides a manufacturing process for an integrated cap specifically for aluminum-cased resistors, including the following steps:

[0075] Low-carbon steel wire with a diameter of 2.0mm is selected as raw material. First, one end of the low-carbon steel wire is formed into a cap body by continuous stamping. Then, the material is cut and the other end that is not stamped is retained as a lead wire. Then, the end of the lead wire is flattened and punched, that is, a 2.0mm diameter mounting hole is punched in the flat part to obtain a bare one-piece cap.

[0076] Add 800.0 parts of deionized water to the plating tank, then add 80.0 parts of methanesulfonic acid and 40.0 parts of tin methanesulfonate, stir to dissolve, then add 0.8 parts of sodium 3-mercapto-1-propanesulfonate and 1.2 parts of catechol, and add deionized water to bring the total water mass to 1000.0 parts. Mix well and heat to a constant temperature of 45°C to prepare the high-temperature anchoring solution for tank A. In another plating tank, add 800.0 parts of deionized water, then add 80.0 parts of methanesulfonic acid and 40.0 parts of tin methanesulfonate, stir to dissolve, then add 1.5 parts of branched polyethyleneimine A, and add deionized water to bring the total water mass to 1000.0 parts. Mix well and control the temperature to 25°C to prepare the low-temperature pulse solution for tank B. This completes the preparation of the dual-tank pure tin electroplating solution.

[0077] The bare integrated caps were subjected to a series of pretreatments, including alkaline degreasing at 50°C for 5 minutes, water washing, acid washing with 10% dilute sulfuric acid at room temperature for 2 minutes, and water washing, before being loaded into a barrel plating machine.

[0078] First, immerse it in tank A at 45°C and a cathode DC current density of 0.5 A / dm³. 2 Under the specified conditions, deep hole accelerator implantation was completed in 3 minutes using a barrel plating process; subsequently, the barrel was removed from tank A and air-transferred for 15 seconds; it was then rapidly immersed in tank B at 25°C using an asymmetric reverse pulse power supply with a forward current density of 1.5 A / dm³. 2 Reverse current density 4.5 A / dm 2 Under the conditions of 100ms forward time and 10ms reverse time, the tube is plated for 12 minutes; then it is taken out, washed with water and dried by centrifugal drying with hot air at 80℃ to obtain an integrated cap for aluminum-cased resistors.

[0079] Example 2:

[0080] This embodiment provides a manufacturing process for an integrated cap specifically for aluminum-cased resistors, including the following steps:

[0081] Low-carbon steel wire with a diameter of 1.8mm is selected as raw material. First, one end of the low-carbon steel wire is formed into a cap body by continuous stamping. Then, the material is cut and the other end that is not stamped is retained as a lead wire. Next, the end of the lead wire is flattened and punched, that is, a mounting hole with a diameter of 1.8mm is punched in the flat part to obtain a bare one-piece cap.

[0082] Add 800.0 parts of deionized water to the plating tank, then add 70.0 parts of methanesulfonic acid and 35.0 parts of tin methanesulfonate sequentially, stir to dissolve, then add 1.0 part of sodium 3-mercapto-1-propanesulfonate and 1.0 part of catechol, and add deionized water until the total water mass is 1000.0 parts. Mix well and heat to a constant temperature of 40°C to prepare the high-temperature anchoring solution for tank A. In another plating tank, add 800.0 parts of deionized water, then add 70.0 parts of methanesulfonic acid and 35.0 parts of tin methanesulfonate sequentially, stir to dissolve, then add 2.0 parts of branched polyethyleneimine B, and add deionized water until the total water mass is 1000.0 parts. Mix well and control the temperature to 20°C to prepare the low-temperature pulse solution for tank B. This completes the preparation of the dual-tank pure tin electroplating solution.

[0083] The bare integrated caps were subjected to a series of pretreatments, including alkaline degreasing at 45°C for 8 minutes, water washing, acid washing with 8% dilute sulfuric acid at room temperature for 3 minutes, and water washing, before being loaded into a barrel plating machine.

[0084] First, it is immersed in tank A at 40°C and a cathode DC current density of 0.4 A / dm³. 2 Under the specified conditions, deep hole accelerator implantation was completed in 4 minutes using a barrel plating process; subsequently, the barrel was removed from tank A and transferred in air for 20 seconds; it was then rapidly immersed in tank B at 20°C using an asymmetric reverse pulse power supply with a forward current density of 1.2 A / dm³. 2 Reverse current density 3.6 A / dm 2 The aluminum-cased resistor is barrel-plated for 14 minutes under the conditions of 80ms forward time and 15ms reverse time; then it is removed, washed with water, and dried by centrifugal drying with hot air at 75℃ to obtain the integrated cap for aluminum-cased resistors.

[0085] Example 3:

[0086] This embodiment provides a manufacturing process for an integrated cap specifically for aluminum-cased resistors, including the following steps:

[0087] Low-carbon steel wire with a diameter of 2.2mm is selected as raw material. First, one end of the low-carbon steel wire is formed into a cap body by continuous stamping. Then, the material is cut and the other end that is not stamped is retained as a lead wire. Next, the end of the lead wire is flattened and punched, that is, a 2.2mm diameter mounting hole is punched in the flat part to obtain a bare one-piece cap.

[0088] Add 800.0 parts of deionized water to the plating tank, then add 90.0 parts of methanesulfonic acid and 45.0 parts of tin methanesulfonate sequentially, stir to dissolve, then add 1.2 parts of sodium 3-mercapto-1-propanesulfonate and 1.5 parts of catechol, and add deionized water to bring the total water mass to 1000.0 parts. Mix well and heat to a constant temperature of 50°C to prepare the high-temperature anchoring solution for tank A. In another plating tank, add 800.0 parts of deionized water, then add 90.0 parts of methanesulfonic acid and 45.0 parts of tin methanesulfonate sequentially, stir to dissolve, then add 1.0 part of branched polyethyleneimine C, and add deionized water to bring the total water mass to 1000.0 parts. Mix well and control the temperature to 28°C to prepare the low-temperature pulse solution for tank B. This completes the preparation of the dual-tank pure tin electroplating solution.

[0089] The bare integrated caps were subjected to a series of pretreatments, including alkaline degreasing at 55°C for 4 minutes, water washing, pickling with 12% dilute sulfuric acid at room temperature for 1.5 minutes, and water washing, before being loaded into a barrel plating machine.

[0090] First, immerse it in tank A at 50°C and a cathode DC current density of 0.6 A / dm³. 2 Under the specified conditions, deep hole accelerator implantation was completed in 2 minutes using a barrel plating process; subsequently, the barrel was removed from tank A and transferred in air for 10 seconds; it was then rapidly immersed in tank B at 28°C using an asymmetric reverse pulse power supply with a forward current density of 1.8 A / dm³. 2 Reverse current density 5.4 A / dm 2 The aluminum-cased resistor-specific integrated cap is obtained by barrel plating for 10 minutes under the conditions of 120ms forward time and 8ms reverse time; after removal, it is washed with water and dried by centrifugal drying with hot air at 85℃.

[0091] Example 4:

[0092] This embodiment provides a manufacturing process for an integrated cap specifically for aluminum-cased resistors, including the following steps:

[0093] Low-carbon steel wire with a diameter of 1.6mm is selected as raw material. First, one end of the low-carbon steel wire is formed into a cap body by continuous stamping. Then, the material is cut and the other end that is not stamped is retained as a lead wire. Next, the end of the lead wire is flattened and punched, that is, a 1.5mm diameter mounting hole is punched in the flat part to obtain a bare one-piece cap.

[0094] Add 800.0 parts of deionized water to the plating tank, then add 75.0 parts of methanesulfonic acid and 38.0 parts of tin methanesulfonate sequentially, stir to dissolve, then add 0.5 parts of sodium 3-mercapto-1-propanesulfonate and 0.8 parts of catechol, and add deionized water until the total water mass is 1000.0 parts. Mix well and heat to a constant temperature of 48°C to prepare the high-temperature anchoring solution for tank A. In another plating tank, add 800.0 parts of deionized water, then add 75.0 parts of methanesulfonic acid and 38.0 parts of tin methanesulfonate sequentially, stir to dissolve, then add 1.8 parts of branched polyethyleneimine D, and add deionized water until the total water mass is 1000.0 parts. Mix well and control the temperature to 22°C to prepare the low-temperature pulse solution for tank B. This completes the preparation of the dual-tank pure tin electroplating solution.

[0095] The bare integrated caps were subjected to a series of pretreatments, including alkaline degreasing at 50°C for 6 minutes, water washing, acid washing with 10% dilute sulfuric acid at room temperature for 2.5 minutes, and water washing, before being loaded into a barrel plating machine.

[0096] First, it is immersed in tank A at 48°C and a cathode DC current density of 0.5 A / dm³. 2 Under the specified conditions, deep hole accelerator implantation was completed in 3 minutes using a barrel plating process; subsequently, the barrel was removed from tank A and transferred in air for 18 seconds; it was then rapidly immersed in tank B at 22°C using an asymmetric reverse pulse power supply with a forward current density of 1.6 A / dm³. 2 Reverse current density 4.8 A / dm 2 The aluminum-cased resistor-specific integrated cap is obtained by barrel plating for 11 minutes under the conditions of a forward time of 90ms and a reverse time of 12ms; after removal, it is washed with water and dried by centrifugal drying with hot air at 80℃.

[0097] Comparative Example 1:

[0098] Compared with Example 1, the difference is that the components of tank A and tank B are combined into a single electroplating solution, that is, the same solution contains 0.8 parts of sodium 3-mercapto-1-propanesulfonate, 1.2 parts of catechol and 1.5 parts of branched polyethyleneimine A. The solution is directly subjected to continuous barrel plating with a pulse power supply at 25°C for 15 minutes, eliminating the dual-tank step-by-step and air transfer steps. All other steps are the same.

[0099] Comparative Example 2:

[0100] Compared with Example 1, the difference is that the temperature of tank A is reduced from 45°C to 25°C, the same as that of tank B, while the rest are the same.

[0101] Comparative Example 3:

[0102] The difference from Example 1 is that no catechol was added when preparing tank A, but everything else is the same.

[0103] Comparative Example 4:

[0104] Compared to Example 1, the difference is that the asymmetric reverse pulse power supply is eliminated during electroplating in tank B, and a cathode DC current density of 0.95 A / dm is used throughout the process. 2 Barrel plating is performed, and everything else is the same.

[0105] Comparative Example 5:

[0106] The difference from Example 1 is that branched polyethyleneimine A was not added when preparing tank B, but all other aspects are the same.

[0107] Test Example 1:

[0108] Take 500 mL each of the high-temperature colonization solution in tank A prepared in Example 1, the low-temperature pulse solution in tank B prepared in Example 1, and the single-tank mixed solution prepared in Comparative Example 1, and place them in three constant-temperature water bath jacketed electrolytic cells.

[0109] The temperature of the high-temperature colonization solution in tank A prepared in Example 1 was set and maintained at 45°C during the test, and the temperature of the low-temperature pulse solution in tank B prepared in Example 1 and the single-tank mixed solution prepared in Comparative Example 1 were set and maintained at 25°C during the test.

[0110] A standard three-electrode system is used to connect to the electrochemical workstation, with a usable area of ​​1 cm². 2 A pretreated pure copper sheet is used as the working electrode, with a surface area of ​​10 cm². 2 A pure tin plate was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode.

[0111] Turn on the electrochemical workstation and perform chronoamperometry tests. Apply a constant cathode polarization potential of -0.6V to the high-temperature colonization solution in tank A prepared in Example 1, the low-temperature pulsed solution in tank B prepared in Example 1, and the single-tank mixed solution prepared in Comparative Example 1. Record the response data of the cathode current density changing with time within the first 120 seconds of the polarization process. The sampling frequency is set to record a stable value once every 10 seconds.

[0112] After the chronoamperometry test was completed, the electrochemical impedance spectroscopy module of the electrochemical workstation was used to perform electrochemical impedance spectroscopy tests on the high-temperature colonization solution in tank A prepared in Example 1, the low-temperature pulsed solution in tank B prepared in Example 1, and the single-tank mixed solution prepared in Comparative Example 1 at open circuit potential. The test frequency range was set from 100kHz to 0.1Hz, and the AC excitation signal amplitude was set to 10mV to obtain the impedance characteristics of the interfacial liquid film.

[0113] Table 1: Time Response Data of Cathode Current Density under Constant Polarization Potential

[0114] Polarization time (s) <![CDATA[Example 1-A Current density of high-temperature planting solution in tank (A / dm 2 )]]> <![CDATA[Example 1-B Low-temperature pulsed liquid current density in the tank (A / dm 2 )]]> <![CDATA[Comparative Example 1 - Current Density of Single-tank Mixed Solution (A / dm 2 )]]> 10 -1.52 -0.48 -1.14 20 -1.47 -0.53 -0.82 30 -1.49 -0.49 -1.76 40 -1.55 -0.51 -1.05 50 -1.51 -0.50 -1.88 60 -1.48 -0.47 -0.76 70 -1.53 -0.52 -1.62 80 -1.46 -0.48 -0.91 90 -1.50 -0.54 -1.85 100 -1.54 -0.50 -0.68 110 -1.49 -0.49 -1.47 120 -1.51 -0.51 -0.83

[0115] According to Table 1 and Figure 1It can be seen that, under a constant polarization potential of -0.6V, the high-temperature colonization solution in tank A prepared in Example 1 and the low-temperature pulsed solution in tank B prepared in Example 1 exhibited relatively concentrated data distribution ranges in their respective cathode current densities within a 120-second test cycle. Specifically, the current density distribution of the high-temperature colonization solution in tank A prepared in Example 1 was -1.46 A / dm³. 2 up to -1.55A / dm 2 Between these values, the current density distribution of the low-temperature pulsed liquid in tank B prepared in Example 1 was -0.47 A / dm². 2 up to -0.54A / dm 2 This suggests that in an additive system with a single dominant property, a stable mass transport state can be established at the electrode interface layer. In contrast, the cathode current density of the single-cell mixture prepared in Comparative Example 1 is -0.68 A / dm³. 2 up to -1.88A / dm 2 They exhibit irregular fluctuations.

[0116] Combination Figure 1 The electrochemical impedance spectroscopy features provided show that the high-temperature colonization solution in tank A prepared in Example 1 and the low-temperature pulsed solution in tank B prepared in Example 1 both exhibit semi-circular curves with a single capacitive arc characteristic, indicating that the interfacial charge transfer process is relatively stable; while the impedance spectrum curve of the single-tank mixed solution prepared in Comparative Example 1 shows obvious distortion characteristics and scattered data points in the mid-to-low frequency region.

[0117] The temporal polarization characteristics summarized in Table 1 and Figure 1 Frequency domain impedance characteristic analysis suggests that small molecule promoters and large molecule inhibitors in a single electrolytic cell system will exhibit competitive adsorption tendencies on the electrode surface, causing the interface layer to be in an unsteady polarization state. The experimental results of Test Example 1 provide theoretical test support for the multi-component additive electrochemical impedance conflict at the metal interface in the multi-cell treatment scheme.

[0118] Test Example 2:

[0119] Bare cap samples that have undergone degreasing and acid washing according to the pretreatment process were immersed in the high-temperature colonization solution A prepared in Example 1 and the high-temperature colonization solution A prepared in Comparative Example 3, respectively, at 45°C and a cathode DC current density of 0.5 A / dm³. 2 Under these conditions, electroplating is performed for 3 minutes.

[0120] The bare cap sample treated in step 1 was extracted from the high-temperature colonization solution in tank A prepared in Example 1 and the high-temperature colonization solution in tank A prepared in Comparative Example 3, and exposed to room temperature air for 15 seconds. After exposure, the surface of the bare cap sample was rinsed with room temperature deionized water for 30 seconds, and then the surface of the bare cap sample was dried with high-purity nitrogen.

[0121] The dried bare cap sample was placed in the vacuum test chamber of an X-ray photoelectron spectroscopy (XPS) instrument. High-resolution narrow-scan measurements of the Sn3d core energy level on the sample surface were performed within a binding energy range of 480 eV to 495 eV. After the measurements, the characteristic peaks of Sn-3d5 / 2 were subjected to peak fitting to calculate the divalent tin Sn. 2+ With tetravalent tin Sn 4+ The integral area ratio of characteristic peaks is used to assess the degree of oxidation on the sample's electrode surface.

[0122] After the high-resolution narrow scanning of the surface is completed, the argon ion gun equipped with the X-ray photoelectron spectrometer is turned on, the etching energy is set to 2kV, and in-situ layer-by-layer peeling etching is performed on the surface of the bare monolithic cap sample. The signal of the O1s characteristic peak is collected at the set etching time nodes, and the change data of the relative atomic percentage of oxygen element on the surface of the bare monolithic cap sample with the argon ion etching time is recorded to evaluate the longitudinal extension depth of the oxidation reaction into the coating.

[0123] Table 2: Fitting data of Sn-3d5 / 2 characteristic peaks on the surface of bare cap samples after air exposure and transfer.

[0124] Experimental subjects <![CDATA[Sn 2+ Binding energy (eV) <![CDATA[Sn 2+ Peak area percentage (%) <![CDATA[Sn 4+ Binding energy (eV) <![CDATA[Sn 4+ Peak area percentage (%) Samples processed in Example 1 486.21 91.4 487.12 8.6 Samples treated in Comparative Example 3 486.18 43.7 487.25 56.3

[0125] According to Table 2 and Figure 2 It can be seen that, after 15 seconds of air transfer simulation, the Sn extracted from the sample electrode surface of the sample treated in Example 1... 2+ The area ratio of characteristic peaks remained at 91.4%, Sn 4+ The characteristic peak area ratio was 8.6%. The sample treated in Comparative Example 3, after the same air exposure without the addition of catechol, showed Sn on the sample surface. 2+ The characteristic peak area ratio is 43.7%, Sn 4+ The characteristic peak area ratio is 56.3%. The above data characteristics suggest that when the tin plating layer with the attached electroplating film is in an oxygen-rich environment, divalent tin ions tend to transform into tetravalent tin; while the formulation state of Example 1 shows a tendency to maintain a low oxidation state distribution on the metal surface.

[0126] Combination Figure 2 The provided oxygen element depth profile curves show complementary longitudinal distribution patterns. The sample treated in Comparative Example 3 has a higher initial oxygen content on its surface, and even after argon ion etching for more than 40 seconds, a relatively obvious oxygen element signal is still detected in the inner layer, indicating that the oxidation process penetrates and expands in the thickness direction. In contrast, the sample treated in Example 1 has a relatively low oxygen content in its initial state, and the oxygen element signal rapidly decays to near the baseline after 10 seconds of etching, indicating that the oxidation behavior is confined to a shallower area of ​​the interface.

[0127] Based on the combined surface valence distribution data and the longitudinal oxygen penetration depth characteristics, the above performance indicates that the addition of catechol molecules to the high-temperature colonization solution in tank A prepared in Example 1 is beneficial for establishing an interfacial chemical barrier when the metal leaves the liquid surface.

[0128] Test Example 3:

[0129] Twenty aluminum-cased resistor-specific integrated caps prepared in Example 1, 20 aluminum-cased resistor-specific integrated caps prepared in Example 3, and 20 integrated caps prepared in Comparative Example 2, 4, and 5 were collected as test samples.

[0130] Turn on the X-ray fluorescence thickness gauge to preheat it, and use a standard pure tin thickness calibration sheet to perform a benchmark calibration on the X-ray fluorescence thickness gauge. Adjust the diameter of the collimator spot of the thickness gauge to 0.1 mm.

[0131] For each example and comparative example of the test sample, three characteristic positions were selected for test positioning: position A was set deep inside the inner wall of the punched mounting hole at the end of the lead wire, position B was set at the straight surface at the center of the flattened area at the end of the lead wire, and position C was set at the outermost sharp corner edge of the flattened end.

[0132] X-ray fluorescence excitation tests were performed on each of the 20 selected test samples at positions A, B, and C. During the test, not only was the absolute value of the tin coating thickness calculated and output by the built-in software of the X-ray fluorescence thickness gauge recorded, but the original pulse count energy distribution data of the characteristic fluorescence spectrum of tin element received by the detector at a characteristic energy calibrated around 3.44 keV was also exported.

[0133] The average thickness distribution data of each test object at different locations were compiled and entered into a table. The original X-ray fluorescence energy spectrum curves of typical test samples at corresponding locations were extracted and compared and analyzed to evaluate the influence of different formulations and electrical parameter combinations on the local deposition rate.

[0134] Table 3: Space Thickness Distribution Data of Integrated Caps Prepared by Different Processes

[0135] Experimental subjects Location A: Thickness (μm) at depth inside the circular hole Location B: Center thickness of the flat zone (μm) Location C: Outer edge thickness (μm) One-piece cap prepared in Example 1 4.82 5.16 5.41 The one-piece cap prepared in Example 3 4.73 5.08 5.25 The one-piece cap prepared in Comparative Example 2 0.91 5.22 5.68 One-piece cap prepared in Comparative Example 4 4.66 5.18 11.83 One-piece cap prepared in Comparative Example 5 3.75 7.14 13.56

[0136] According to Table 3 and Figure 3 and Figure 4 It can be seen that the coating thickness of the integrated cap prepared in Example 1 and the integrated cap prepared in Example 3 shows a relatively similar distribution characteristic at the three test locations. The thickness of the integrated cap prepared in Example 1 ranges from 4.82 μm deep inside the blind hole to 5.41 μm at the outer edge, with the thickness difference distributed within the range of 0.59 μm. This distribution tendency suggests that the set two-step transfer scheme can form a deposition coating with a relatively uniform thickness distribution on the microscopic three-dimensional morphology with structural shielding.

[0137] exist Figure 3 In Comparative Example 2, the integrated cap prepared in Comparative Example 2 showed a weak tin characteristic peak signal near 3.44 keV, which corresponds to the 0.91 μm missing plating data in Table 3. This indicates that the room temperature environment limits the gas-liquid exchange efficiency of the drug solution containing accelerator inside the micropores. In contrast, the integrated cap prepared in Example 1 showed an obvious normal fluorescence response peak, indicating that increasing the temperature of the A tank can reduce the fluid viscosity, which helps the small molecule accelerator penetrate into the blind zone for adsorption and colonization.

[0138] exist Figure 4 In the comparison, the SnLα characteristic peak intensity of the integrated cap prepared in Comparative Example 4 and Comparative Example 5 showed an abnormally high state, which corresponds to the edge thickening phenomenon of more than 11 μm in Table 3. This energy signal characteristic suggests that in the absence of periodic anodic reverse current dissolution process and steric hindrance of macromolecular polymer, excessive reduction and accumulation of metal ions will occur at the external tip position. The fluorescence peak intensity of the integrated cap prepared in Example 1 at the same position is at a relatively controlled level. This performance verifies that the reverse pulse parameter combined with the polymer inhibitor can produce a superimposed inhibitory effect of physical cutting and chemical inhibition on the growth tendency of edge dendrites.

[0139] Test Example 4:

[0140] Fifty aluminum-cased resistor-specific integrated caps prepared in Example 1, 50 aluminum-cased resistor-specific integrated caps prepared in Example 3, and 50 aluminum-cased resistor-specific integrated caps prepared in Comparative Example 1 and 3 were collected as macroscopic performance test samples.

[0141] Solderability tests were performed on the aluminum-cased resistor integrated caps prepared in Example 1, Example 3, Comparative Example 1, and Comparative Example 3 using a wetting balance tester. The lead-free solder bath temperature was set to 260°C, the immersion depth to 2.0 mm, the immersion speed to 5 mm / s, and the immersion holding time to 10 seconds. The dynamic curve of wetting force changing with time was recorded, and the zero-crossing time and maximum wetting force data during the test were extracted.

[0142] Ten aluminum-cased resistor-specific integrated caps prepared in Example 1, Example 3, Comparative Example 1, and Comparative Example 3 were selected for thermal shock peel resistance tests. The test objects were placed in a constant temperature baking oven at a set temperature of 260°C and baked for 3 minutes. They were then removed and cooled to room temperature. A 1mm × 1mm grid test area was marked on the flattened straight area of ​​the test object using a process blade. Then, standard test tape was tightly attached to the grid test area and quickly pulled at a 60-degree angle. The peeling situation was observed under a microscope and the percentage of the coating peeled off was calculated.

[0143] The contact resistance of the aluminum-shell resistor-specific integrated caps prepared in Example 1, Example 3, Comparative Example 1, and Comparative Example 3 was tested using a micro resistance tester. The two ends of the test fixture were connected to the end of the lead wire and the outer edge of the iron cap body, respectively, and the absolute value of the resistance after the reading stabilized was recorded.

[0144] For the aluminum-shell resistor-specific integrated cap prepared in Example 1 and the aluminum-shell resistor-specific integrated cap prepared in Comparative Example 3, a two-dimensional probe scanning microscopy system was used to perform micro-area electrical mapping tests on the surface of the flattened area. The scanning area was set to 100μm×100μm and the probe step resolution was 2μm. The local contact resistance values ​​of each micro-area coordinate point were recorded to generate a two-dimensional spatial electrical distribution matrix, which was used to analyze the microscopic uniformity and hidden defects of the interface electrical transmission.

[0145] Table 4: Macroscopic Application Performance Test Data of Aluminum Shell Resistor Integrated Caps Prepared by Different Processes

[0146] Experimental subjects Zero-crossing time of wetting (s) Maximum wetting force (mN) Coating peeling rate after thermal shock (%) Absolute value of contact resistance (mΩ) Example 1: Aluminum-cased resistor-specific integrated cap prepared 0.57 3.42 0 2.14 Example 3: Aluminum-cased resistor-specific integrated cap prepared 0.62 3.28 0 2.37 Comparative Example 1: Aluminum-cased resistor-specific integrated cap 2.81 1.15 8.5 4.86 Comparative Example 3: Aluminum-cased resistor-specific integrated cap 1.14 2.06 54.2 8.53

[0147] According to Table 4 and Figure 5 and Figure 6 It can be seen that the aluminum-cased resistor-specific integrated cap prepared in Example 1 and the aluminum-cased resistor-specific integrated cap prepared in Example 3 exhibit excellent macroscopic application reliability. The zero-crossing time is controlled within 0.62 seconds, indicating that the surface metallurgical wetting reaction starts rapidly. After experiencing a rapid thermal stress shock at 260°C, the coating peeling rate of the aluminum-cased resistor-specific integrated cap prepared in Example 1 and the aluminum-cased resistor-specific integrated cap prepared in Example 3 is 0, and the absolute value of the macroscopic overall contact resistance remains below 2.37mΩ.

[0148] In contrast, the aluminum-cased resistor-specific integrated cap prepared in Comparative Example 3, after undergoing the same thermal shock test, showed a 54.2% coating peeling area on its surface, while the absolute value of the overall macroscopic contact resistance increased to 8.53 mΩ.

[0149] exist Figure 5 In Example 1, the local contact resistance distribution on the surface of the aluminum-shell resistor-specific integrated cap showed a uniform and consistent light gray area, without obvious impedance abrupt changes. This suggests that the interface sealing mechanism in the slotting process prevents impurities from penetrating and forms a continuous and dense metallurgical interface. Figure 6 In Comparative Example 3, the surface of the aluminum-shell resistor-specific integrated cap prepared showed an increase in basic impedance, as well as multiple dark black high-impedance patches and islands. This spatial electrical heterogeneity strongly suggests that during the process of the substrate being removed from the A-cell and exposed to air for transfer, the exposed tin ions underwent local oxidation, which in turn formed unevenly distributed tetravalent tin oxide inclusions on the surface.

[0150] Based on the above mechanical and micro-area electrical analyses, the non-uniform insulating oxide islands inside the aluminum-shell resistor-specific integrated cap prepared in Comparative Example 3 not only hinder the longitudinal transmission of electrons, leading to increased contact resistance, but also, under high-temperature thermal shock conditions, these oxide patches exhibit a significant difference in thermal expansion coefficients with the surrounding metal lattice, which can become crack initiation sources for thermal stress concentration. In contrast, the aluminum-shell resistor-specific integrated cap prepared in Example 1, due to the effect of the anti-oxidation barrier in the formula, eliminates inclusions at the internal interface, thereby exhibiting a high degree of structural stability and electrical conductivity on a macroscopic level.

[0151] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A one-piece cap specifically for aluminum-cased resistors, characterized in that, Includes a bare integrated cap and a pure tin electroplated layer covering the surface of the bare integrated cap; The pure tin electroplating layer is formed by step-by-step electroplating of a dual-tank pure tin electroplating solution composition comprising a high-temperature anchoring solution in tank A and a low-temperature pulse solution in tank B. Based on a total weight of 1000 parts of deionized water, the raw materials of the high-temperature colonization solution in tank A include: 70 to 90 parts of methanesulfonic acid; 35 to 45 parts of tin methanesulfonate; Sodium 3-mercapto-1-propanesulfonate, 0.5 to 1.2 parts; 0.8 to 1.5 parts of catechol; Based on a total weight of 1000 parts of deionized water, the raw materials for the low-temperature pulsed liquid in tank B include: 70 to 90 parts of methanesulfonic acid; 35 to 45 parts of tin methanesulfonate; 1.0 to 2.0 parts of branched polyethyleneimine.

2. The integrated cap for aluminum-cased resistors according to claim 1, characterized in that, The branched polyethyleneimine has a weight-average molecular weight of 600 to 1000.

3. The integrated cap for aluminum-cased resistors according to claim 1, characterized in that, The branched polyethyleneimine is made from the following raw materials in parts by weight: 85.0 to 115.0 parts of deionized water; 1.5 to 2.4 parts of p-toluenesulfonic acid monohydrate; 6.5 to 11.2 parts of ethyleneimine monomer.

4. The integrated cap for aluminum-cased resistors according to claim 1, characterized in that, The bare integrated cap is made of low carbon steel wire with a diameter of 1.6 to 2.2 mm through continuous stamping and integral forming. One end of the bare integrated cap is the formed cap body, and the other end is the retained lead wire. The end of the lead wire is provided with a flattened part, and the flattened part is punched with a mounting round hole with a diameter of 1.5 to 2.2 mm.

5. A manufacturing process for an integrated cap for aluminum-cased resistors according to any one of claims 1-4, characterized in that, Includes the following steps: Low-carbon steel wire is selected as raw material. First, one end of the low-carbon steel wire is formed into a cap body by continuous stamping. Then, the material is cut and the other end that is not stamped is retained as a lead wire. Then, the end of the lead wire is flattened and punched to obtain a bare one-piece cap. The high-temperature colonization solution for tank A and the low-temperature pulse solution for tank B were prepared separately. The bare cap is subjected to pretreatment in sequence, including alkaline degreasing, water washing, dilute sulfuric acid pickling at room temperature, and water washing. The bare integrated cap, after the pretreatment, is first immersed in the high-temperature stationary solution in tank A under heating for cathodic DC barrel plating; then the solution is removed and exposed to air for a set time; then it is quickly immersed in the low-temperature pulsed solution in tank B under cooling, and barrel plating is performed using an asymmetric reverse pulse power supply; finally, it is taken out, washed with water and dried by hot air centrifugation to obtain the aluminum shell resistor-specific integrated cap.

6. The manufacturing process of the integrated cap for aluminum-cased resistors according to claim 5, characterized in that, In the pretreatment step, the following steps are performed sequentially: alkaline degreasing at 45 to 55°C for 4 to 8 minutes, water washing, acid washing with dilute sulfuric acid at room temperature with a mass concentration of 8% to 12% for 1.5 to 3 minutes, and water washing.

7. The manufacturing process of the integrated cap for aluminum-cased resistors according to claim 5, characterized in that, In the cathode DC barrel plating step, the constant temperature of the high-temperature planting solution in tank A is controlled at 40 to 50°C, and the cathode DC current density is 0.4 to 0.6 A / dm³. 2 The barrel plating time is 2 to 4 minutes.

8. The manufacturing process of the integrated cap for aluminum-cased resistors according to claim 5, characterized in that, The set time for the naked cap to be exposed to air is controlled between 10 and 20 seconds.

9. The manufacturing process of the integrated cap for aluminum-cased resistors according to claim 5, characterized in that, In the barrel plating step using an asymmetric reverse pulse power supply, the constant temperature of the low-temperature pulse liquid in tank B is controlled to be 20 to 28°C; the parameters of the asymmetric reverse pulse power supply are set as follows: forward current density 1.2 to 1.8 A / dm³. 2 Reverse current density 3.6 to 5.4 A / dm 2 The forward time is 80 to 120 ms, the reverse time is 8 to 15 ms, and the continuous barrel plating time is 10 to 14 minutes.

10. The manufacturing process of the integrated cap for aluminum-cased resistors according to claim 5, characterized in that, In the hot air centrifugal drying step, hot air with a temperature controlled at 75 to 85°C is used to centrifuge and dry the finished product after washing.